Snow Buntings Maintain Winter-Level Cold Endurance While Migrating to the High Arctic - Le Pogam, Audrey; O’Connor, Ryan S.; Love, Oliver P.; Drolet, Justine; Régimbald, Lyette; Roy, Gabrielle; Laplante, Marie-Pier; Berteaux, Dominique; Tam, Andrew; Vézina, François (Frontiers in Ecology and Evolution, 2021)
Arctic breeding songbirds migrate early in the spring and can face winter environments requiring cold endurance throughout their journey. One such species, the snow bunting (Plectrophenax nivalis), is known for its significant thermogenic capacity. Empirical studies suggest that buntings can indeed maintain winter cold acclimatization into the migratory and breeding phenotypes when kept captive on their wintering grounds. This capacity could be advantageous not only for migrating in a cold environment, but also for facing unpredictable Arctic weather on arrival and during preparation for breeding. However, migration also typically leads to declines in the sizes of several body components linked to metabolic performance. As such, buntings could also experience some loss of cold endurance as they migrate. Here, we aimed to determine whether free-living snow buntings maintain a cold acclimatized phenotype during spring migration. Using a multi-year dataset, we compared body composition (body mass, fat stores, pectoralis muscle thickness), oxygen carrying capacity (hematocrit) and metabolic performance (thermogenic capacity - Msum and maintenance energy expenditure - BMR) of birds captured on their wintering grounds (January-February, Rimouski, QC, 48°N) and during pre-breeding (April-May) in the Arctic (Alert, NU, 82°). Our results show that body mass, fat stores and Msum were similar between the two stages, while hematocrit and pectoralis muscle thickness were lower in pre-breeding birds than in wintering individuals. These results suggest that although tissue degradation during migration may affect flight muscle size, buntings are able to maintain cold endurance (i.e., Msum) up to their Arctic breeding grounds. However, BMR was higher during pre-breeding than during winter, suggesting higher maintenance costs in the Arctic.